Comparison of the mass composition of Coconut Shell in TiO2 towards its characterization for supercapacitor applications - Siagian, Sinta Marito; H. S, Samaria Chrisna; Tampubolon, Ferdinan Rinaldo; Juanta, Palma (Universitas Sanata Dharma, 2024)
This study aims to evaluate the effect of the mass ratio on the capacitance of electrodes made from TiO-based composites. The composites were synthesized using a wet chemical method and applied using the doctor blade technique, incorporating TiO2 and rGO derived from coconut shell activated carbon. Our findings reveal that at a 1:1 mass ratio, the atomic composition of Ti and O was non-uniform, although there was evident adherence of TiO2 elements to the sample surface. In contrast, at mass ratios of 1:3 and 1:5, a decrease in the concentration of Ti atoms and an increase in O atoms were observed, indicating a reduction in Ti oxidation. SEM analysis further revealed that particle size significantly impacts capacitance: smaller particle sizes yielded higher capacitance. In the 1:1 mass variation, the discharge process was protracted, taking up to 29.3 minutes and generating an electrical energy of 0.000413 joules with a capacitance of 489 µF. These insights are pivotal for optimizing the composition and mass ratio, fostering the development of electrode materials characterized by enhanced capacitance and energy efficiency. Such advancements hold promising potential for a range of applications in the energy storage sector.Keywords: Activated Carbon, Capasitance, Supercapacitor